Caesarean sections are associated with sonographic determined fetal size from the second trimester onwards - Kirchengast, Sylvia; Hartmann, Beda (Anthropological Review, 2020)
Human birth represents a critical and life-threatening event in the life of mother and child and is therefore of special importance for anthropological as well as public health research.